Design of low cost IoT enabled embedded control system for covid free smart home. Issue 1 (1st February 2022) - Singh, Khushi; Jindal, Sumit Kumar
Abstract: In the era of automation, the Internet of Things (IoT) has come up as a solution and innovation for many applications to improve the basic facilities required in the day-to-day routine. IoT, itself is the interconnectivity of different physical devices with the help of wireless networks e.g., Bluetooth, Wi-Fi without human intervention. The low-cost embedded control unit for Covid free Smart Home is based on the idea of home automation by keeping the current situation of the Covid pandemic in mind. Irradiation of Ultraviolet C (UVC) spectrum is used to sanitize household goods, where convectional sanitization process is not suitable. Simple home automation means controlling or monitoring different electronic/electrical home appliances, devices, and other such things with smartphones or by doing sensor-based operations. All the required devices are connected with one embedded control unit which is managed through a mobile app. This functionality can be accessed either by manually operating a mobile app or with voice assistants e.g., Alexa or Google Assistant, etc. The basic point of communication among devices is based on real-time sensor inputs, which trigger the devices for action and react as per requirements. Ambient light sensors are used to control the on/off the functionality of lights based on the intensity of light present naturally. In this scenario, lights will be switched off in day mode and switched on in night mode. Advancement in wireless technologies enables the researchers to apply various modes of communications among the sensors, gateway, and applications. Bluetooth, Wireless sensor network (WSN), Wi-Fi, Global system for mobile communication (GSM) are a few of them, which are being used either in sensing nodes or in communication gateway to make home automation free of the wired network.